Possibilities of the QCM method employment to determination of toxic compound concentration in dependence of barrier materials resistance - Otřísal, Pavel; Florus, Stanislav (Vojenské zdravotnické listy, 2012)
This paper points to some aspects of possible usage of a QCM method within a set of toxic compounds permeated concentration based on a permeation curves rate and after underdone calibration of a measurement system. Presented assesses can be used not only in favour of the Czech Armed Forces Chemical Corps specialists but subsequently also in favour of personnel protection for those working in an area with toxic compounds appearance.
Keywords: zbraně hromadného ničení; Weapons of Mass Destruction; Protective Devices; Chemical Warfare Agents; mikrorovnovážné techniky křemenného krystalu; kalibrace; Calibration; chemické bojové látky; ozbrojené síly; Military Personnel; ochranné prostředky; Quartz Crystal Microbalance Techniques